Pemberdayaan Masyarakat pada Penerapan Konstruksi Bangunan Sipil di Kelurahan Anduonohu Kota Kendari - Welendo, La; Ngii, Edward; Putra, Adris Ade; Nuhun, Ridwan Syah; Talanipa, Romy; Mahapati, Waode Sitti Warsita; Lalang, Lalang; Kaimuddin, Januar Saleh; Balaka, Rudi; Mursidi, Baso; Makmur, Muammar; Takdir, Riyan Abdillah; Minmahddun, Anafi (Jurnal Pengabdian Masyarakat Ilmu Terapan (JPMIT), 2023)
Community service activities by a team of teaching staff as one form of the tri dharma (Lecturers) of Halu Oleo University, namely carrying out community service, in carrying out community service to provide contributions in the form of knowledge about pontesi and infrastructure development to improve the welfare of the community in the sub-district Anduonohu Kendari City. Anduonohu Village is a potential area and has sufficient natural resources, in this case potential agricultural land (fertile land), but road access to the Village needs serious attention from all parties. Therefore, we, as a team of lecturers, provide service to contribute work/products and understanding to the community regarding infrastructure development, especially improving farm roads as access for community movement to support economic, social, educational and other activities. The implementation process in this service activity is an implementation technique according to the availability of resources from the service implementation team in the form of outreach to the community, farmers and local government by prioritizing science. This Community Partnership Program (PKM) is delivered in community service activities as an impact of increasing community knowledge, especially in developing infrastructure in Anduonohu Village, Kendari City. The methods used in this activity are example providing, direct or face to face discussions with the community, as well as field applications. in infrastructure development (repairing village roads). It is hoped that this service program activity can provide knowledge and understanding to the community regarding the application of science to benefit society.